2017
DOI: 10.1161/atvbaha.117.309768
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of MicroRNA-33 Attenuates Inflammation and Abdominal Aortic Aneurysm Formation via Several Anti-Inflammatory Pathways

Abstract: These data strongly suggest that inhibition of miR-33 will be effective as a novel strategy for treating AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 38 publications
3
55
0
1
Order By: Relevance
“…Supporting this result, gene expression analysis confirmed no significant difference in the expression of Abca1 or Abcg1 in macrophages obtained from miR-33 KOKI mice compared with miR-33 WT mice ( Figure 6B and 6C). Although previous reports also suggested the participation of miR-33 in macrophage inflammatory phenotypes, 15,16 inflammatory gene expression patterns were similar between macrophages obtained from miR-33 KOKI mice compared with miR-33 WT mice ( Figure 6D).…”
Section: Relevant Functions Of Mir-33a and Mir-33b In Macrophagessupporting
confidence: 54%
See 1 more Smart Citation
“…Supporting this result, gene expression analysis confirmed no significant difference in the expression of Abca1 or Abcg1 in macrophages obtained from miR-33 KOKI mice compared with miR-33 WT mice ( Figure 6B and 6C). Although previous reports also suggested the participation of miR-33 in macrophage inflammatory phenotypes, 15,16 inflammatory gene expression patterns were similar between macrophages obtained from miR-33 KOKI mice compared with miR-33 WT mice ( Figure 6D).…”
Section: Relevant Functions Of Mir-33a and Mir-33b In Macrophagessupporting
confidence: 54%
“…Notably, we and other groups have shown previously that miR-33 potentially affects many biological pathways, including cholesterol homeostasis. [8][9][10][11][12][13][14][15][16][17][18] In vivo deletion or inhibition of miR-33 using antisense oligonucleotide improved the serum cholesterol profile and enhanced cholesterol reverse transport of not only mice, but also nonhuman primates. These favorable changes in serum cholesterol profile or cholesterol reverse transport reduced atherosclerotic plaque progression in mice.…”
mentioning
confidence: 99%
“…Further, pre-miR-24, anti-miR-29b and anti-miR-33 treatment can attenuate aneurysm in mouse models. 187,192,194 These results strongly reveal that miRNA treatment may be a novel and useful therapeutic strategy for AA.…”
Section: Aneurysmmentioning
confidence: 78%
“…It is important to note that in this work, the presence of circulating levels of miR-33a is further characterized, 10 times higher than the levels of miR33b. In the context of IR overlapping with ageing, the circulating levels of the miR-33 family presented in this study have not been previously reported; in this regard, there are two scenarios that we be able to distinguish: first, the reports that precede this study are related to miR-33 intracellular expression (endogenous) or circulating levels in other diseases, 37,38 while in this study we focused on mature (circulating levels) miR-33 in individuals with the novo IR classification, and second, the individuals included in this study were characterized with IR according to a strict system, the Stern criteria; 15 in this sense, we cannot establish controversy with others studies.…”
Section: Discussionmentioning
confidence: 67%